(untitled) (International Journal of Engineering and Computer Science, 2015)
Virtualization means to create a virtual version of a device or resource, such as a server, storage device. Thus the virtualization play good role in the resource provisioning for the cloud controller. There is large scope in the resources provisioning management in Virtualized Cloud. This paper presents a process of analysis of performance in terms of CPU Time, Memory usage for the different virtual machines of Ubuntu, RHEL 6.0 and Win7’s using the KVM hypervisor in hybrid virtualization environment. The main objective is to find the performance parameters of various virtual machines on a single host and proceeds to find an effective choice for the collection of effective virtual machine for the cloud user.